2010
DOI: 10.4049/jimmunol.0900047
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Is Necessary for Host Protection against Acute-Phase Trypanosoma cruzi Infection

Abstract: Material Supplementary 7.DC1http://www.jimmunol.org/content/suppl/2010/06/18/jimmunol.090004

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
133
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 50 publications
5
133
0
6
Order By: Relevance
“…Infants diagnosed for T. cruzi infection later after birth (i.e., 6-12 mo of age) had not only lower IFN-g levels but also higher IL-17A and IL-6 levels throughout the follow-up period than children diagnosed at 1 mo of age. We speculate that, as reported in experimental models of T. cruzi infection, IL-17 might have a protective role recruiting and activating neutrophils and monocytes required for early control of the pathogen (28,29). Other studies have shown that IL-17 is also crucial in the control of cardiac inflammation and host survival, playing a negative feedback role in the production of IFN-g and chemokines during T. cruzi infection in humans and mice (30).…”
Section: Discussionmentioning
confidence: 99%
“…Infants diagnosed for T. cruzi infection later after birth (i.e., 6-12 mo of age) had not only lower IFN-g levels but also higher IL-17A and IL-6 levels throughout the follow-up period than children diagnosed at 1 mo of age. We speculate that, as reported in experimental models of T. cruzi infection, IL-17 might have a protective role recruiting and activating neutrophils and monocytes required for early control of the pathogen (28,29). Other studies have shown that IL-17 is also crucial in the control of cardiac inflammation and host survival, playing a negative feedback role in the production of IFN-g and chemokines during T. cruzi infection in humans and mice (30).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IL-22 is essential for maintaining mucosal barrier function and for the enhanced epithelial cell proliferation and cytokine production required to control K. pneumoniae infection (9). High levels of IL-17A and IL-22 also strongly correlate with protective immunity in human populations infected with Leishmania donovani (39), and IL-17A 2/2 mice fail to control Trypanosoma cruzi infection, which leads to multiple organ failure and mortality (40). However, to date no protective role for IL-22 has been shown in parasite infections.…”
Section: Discussionmentioning
confidence: 99%
“…We focused our efforts on IL-17A and IL-17F (IL-17A/F), two main factors in the IL-17 protein family that are known to play an important role in antimicrobial host defenses and immunological responses to a variety of infections, including fungi, bacteria, viruses, and parasites (6,15,16,26,29). IL-17A and IL-17F appear to bind the same receptor complexes, comprising IL-17 receptor A and IL-17 receptor C (42,54), and therefore appear to have similar biological functions (16).…”
mentioning
confidence: 99%